Hotel Building Reliability Towards Building Age - Syukri Indrawansyah; Abdullah Abdullah; Cut Zukhrina Oktaviani (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2020)
Abstract: Mahara Hotel is a tourism-supporting facility and infrastructure first established in Central Aceh District in 1999. This 3-story hotel used a reinforced concrete frame structure, and as time goes by, the service capacity of the building would decrease. This condition was suspected to affect quality and user convenience. Anticipate the older age of the building, and better maintenance management is applied so that the proper building’s function can be maintained. The purpose of this study was to assess the reliability of 20 year-established hotel buildings. The method was a descriptive analysis. Data were analyzed based on the guidelines of Technical Procedures for Guidelines for Certificate of Eligibility for Functions (SLF) of Buildings Regulation of Minister of Public Works No. 25/PRT/M/2007. Based on the results, the reliability value of the Mahara Hotel building was unreliable (66.75 %), less than the SLF guidelines (at least 75 %). Some components that caused a low level of reliability to include utility and fire protection components (20.34 %) and accessibility components (3.11 %). The effective and efficient component in increasing the reliability of the building was the utility and fire protection components by not requiring major demolition.Abstrak: Hotel Mahara merupakan sarana dan prasarana penunjang pariwisata yang pertama kali berdiri di Kabupaten Aceh Tengah pada tahun 1999. Hotel berlantai 3 ini menggunakan struktur rangka beton bertulang dan seiring dengan berjalannya waktu, daya layan gedung akan semakin menurun. Kondisi ini ditenggarai akan mempengaruhi kualitas dan kenyamanan pengguna. Untuk mengantisipasi hal tersebut, maka semakin tua umur bangunan, seharusnya didukung dengan penerapan manajemen pemeliharaan yang baik agar kelayakan fungsi dari bangunan dapat dipertahankan. Tujuan dari penelitian ini untuk menilai keandalan bangunan hotel setelah berumur 20 tahun. Metode yang digunakan adalah analisis deskriptif. Data dianalisis berdasarkan panduan Teknis Tata Cara Pedoman Sertifikat Laik Fungsi (SLF) Bangunan Gedung Peraturan Menteri Pekerjaan Umum No. 25/PRT/M/2007. Berdasarkan hasil penelitian, nilai keandalan bangunan gedung Hotel Mahara termasuk tidak andal yaitu sebesar 66.75 %, kurang dari yang dipersyaratkan oleh pedoman SLF tersebut yaitu minimal 75 %. Beberapa komponen yang menyebabkan rendahnya tingkat keandalan anatara lain komponen utilitas dan proteksi kebakaran sebesar 20.34 % serta komponen aksesibilitas sebesar 3.11 %. Komponen yang efektif serta efisien dalam menaikkan tingkat keandalan bangunan gedung tersebut adalah komponen utilitas dan proteksi kebakaran dengan tidak mengharuskan pembongkaran yang besar.